Comparison of Total Phenolic, Flavonois Content, and Antioxidant Activity Artocarpus heterophyllus Lamk. Methanol Extract from Sleman and Bantul District - Pratiwi, Ambar; Susilowati, Riska (Journal of Biotechnology and Natural Science, 2021)
Antioxidant compounds can inhibit free radicals that are harmful to body health. The side effects of natural antioxidant compounds are safer than synthetic antioxidants. The source of natural antioxidant compounds can be obtained from jackfruit because it contains phenolics, flavonoids, sterols, and tannins. The study was conducted to determine the highest total phenolic content, total flavonoids, and antioxidant activity in the methanol extract samples of jackfruit from Sleman and Bantul Regencies. The extraction technique used maceration with methanol (1: 5) solvent. The phenolic content was tested by the Follin-Ciocalteu method at a wavelength of 745 nm, while the flavonoid content was tested using the AlCl3 method at a wavelength of 435 nm. The antioxidant activity was determined by the diphenylpicrylhydrazyl (DPPH) method at a wavelength of 517 nm. The results showed that the total phenolic and flavonoid content of the methanol extract of jackfruit from Bantul Regency was 1.927 m GAE / mg and 0.261 m QE / mg higher than Sleman Regency 1.353 m GAE / mg and 0.0913 m QE / mg and the highest antioxidant activity name in the sample extract from Bantul Regency, the IC50 value was 581.5 mg / mL and based on the results of statistical tests there were significant differences in content. This study concludes that the total phenolic content and total flavonoids as well as the antioxidant activity of the methanol extract of jackfruit from the Bantul Regency were higher than from Sleman Regency.